Solving Economic Dispatch Problems with Practical Constraints Utilizing Differential Search Algorithm - M. H., Sulaiman; Mohd Wazir, Mustafa (2013)
This paper presents a recent swarm intelligence technique namely Differential Search (DS) algorithm in solving Economic Dispatch (ED) problems with considering the practical constraints in power system. DS simulates the Brownian-like random-walk movement used by organisms to migrate. In solving ED problem, DS will find the combination of power scheduling which fulfilling the demand so that the total generation cost can be minimized without violating any constraints. To demonstrate the feasibility of the proposed DS in solving ED problems, two well-known test cases have been used: 6-units and 15-units systems; and compared with various recently published methods in literature. The results of this study show that DS is able to obtain more economical solution than those determined by other methods.